Permodelan Sebaran Air Limbah Pada Ruang Terbuka Hijau di Rumah Sakit Surabaya Menggunakan Modflow - Naufaldy Iqbal Abdillah (Prosiding ESEC, 2023)
Clean water is the main need for people to carry out their daily activities. Communities use clean water by using drilled wells sourced from groundwater, so the quality of groundwater must be maintained so that the well water used is not polluted and dangerous when used. Several sectors are currently disposing of the results of the Wastewater Treatment Plant (WWTP) for watering Green Open Space (RTH) land. One of them is in the health sector or hospitals. Disposal of wastewater to the ground is required to carry out periodic quality control and modeling so that the volume of wastewater does not cause a significant increase in groundwater. This study uses groundwater modeling with the help of MODFLOW-6 software. The purpose of this study is to determine the distribution of wastewater on the ground and the nature of the impact related to the area of distribution, intensity, time, and impact on plants. The parameters of the wastewater tested were TSS, COD, BOD, and Residual Chlorine. While the data needed are elevation, hydraulic conductivity, groundwater level, and wastewater discharge. The results of the simulation carried out for 365 days showed the distribution of contaminants that had been simulated using TSS and COD parameters. The simulation results show that there is the same lateral distribution direction, namely to the west and also leaning to the southeast following the gradient of the land surface and groundwater table. By obtaining a contaminant concentration value below the quality standard, it indicates that the waste used around the observation area is safe for application to the soil.